Lymphagioma of the Tongue: A Case Report - Puttanimon, Santipap; Ploypradit, Chamnarn; Chamusri, Nutchapon; Thosaporn, Wacharaporn; Iamaroon, Anak (Journal of Dentistry Indonesia, 2019)
Lymphangioma is a benign growth caused by developmental malformation of lymphatic vessels that usually occurs within the first two decades of life. The clinical features present as painless, nodular, vesicle-like swellings of the soft tissue, most commonly found on the anterior two-third of the tongue. Histopathology demonstrates multiple dilated lymphatic vessels, containing proteinaceous fluid and occasionally leukocytes. We here reported a case of a seven-year-old Thai male presented with papillary and vesicle-like swelling on the left dorsal tongue for five years. The lesion of the patient was surgically excised under general anesthesia and followed up for six months without signs of recurrences.